Revitalising the rudimentary replacement dentition in the mouse - Popa, Elena M; Buchtova, Marcela; Tucker, Abigail S (Development (Cambridge, England), 2019)
Most mammals have two sets of teeth (diphyodont) - a deciduous dentition replaced by a permanent dentition; however, the mouse possesses only one tooth generation (monophyodont). In diphyodonts, the replacement tooth forms on the lingual side of the first tooth from the successional dental lamina. This lamina expresses the stem/progenitor marker Sox2 and has activated Wnt/β-catenin signalling at its tip. Although the mouse does not replace its teeth, a transient rudimentary successional dental lamina (RSDL) still forms during development. The mouse RSDL houses Sox2-positive cells, but no Wnt/β-catenin signalling. Here, we show that stabilising Wnt/β-catenin signalling in the RSDL in the mouse leads to proliferation of the RSDL and formation of lingually positioned teeth. Although Sox2 has been shown to repress Wnt activity, overexpression of Wnts leads to a downregulation of Sox2, suggesting a negative-feedback loop in the tooth. In the mouse, the first tooth represses the formation of the replacement, and isolation of the RSDL is sufficient to induce formation of a new tooth germ. Our data highlight key mechanisms that may have influenced the evolution of replacement teeth.This article has an associated 'The people behind the papers' interview.
Keywords: Wnt Signaling Pathway; Swine, Miniature; Wnt/β-catenin; Cell Proliferation; Animals; Mice, Transgenic; Mice; Minipig; Tooth; Replacement tooth; signální dráha Wnt; proliferace buněk; Sox2; Swine; Tooth Germ; miniaturní prasata; zubní zárodek; myši transgenní; zvířata; Mammal evolution; prasata; transkripční faktory SOXB1; SOXB1 Transcription Factors; zuby; myši; Mouse molar